Health psychology: a well-being and happiness science - Oblitas Guadalupe, Luis (2008)
Health psychology is tackled, including its conceptual definition, as well as the biopsychosocial model characterizing it. This paper describes evidences on the narrow relationship between beahvior and health, in orden to have a better comprehension of health and disease, as well as of pathogenic and immunogenic behavioral agents. Behaviors promoting health, quality of life, and positive psychology are described in detail. The main applications in health and disease are also anayzed. In conclusion, health psychology is an excellent alternative to generate well.-being and happiness.